Pendampingan Psikososial Melalui Dongeng Inspiratif: Pelatihan Keterampilan Mendongeng untuk Penguatan Mental Masyarakat Pasca Gempa Bumi di Pulau Bawean - Ansori, Ansori; Ilham, Ilham; Mawardi, Imam; Abrory, Lucky; Aminah, Siti (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2024)
Earthquakes are one of the natural disasters that can cause significant physical and psychological damage to humans, especially children. Children are a vulnerable group that requires special attention in dealing with the psychosocial impacts of the post-earthquake in Bawean. The aim of this assistance is expected to be to restore the mental condition of the community and children to normal before the earthquake occurred and motivate children to learn to be patient and encourage the community to be more creative in their efforts to help post-earthquake psychological recovery and to create a positive impact on Bawean residents. The mentoring method uses the Participatory Action Research (PAR) approach, which is a participatory type of partnership with the community (community engagement) in a collaborative process that is explicitly oriented towards social transformation. The results of assistance to the people affected by the Bawean earthquake can relieve anxiety, especially psychological problems in children and the community. The implementation of assistance through inspirational stories, religious counseling and storytelling skills training is a post-earthquake solution in looking at a more positive life for their lives today. especially providing trauma healing assistance to children.